Nourish & Lift Enterprise : High Mobility Wheelchair / Nik Ahmed Aiman Nik Ahmed Jafni...[et al.] - Nik Ahmed Jafni, Nik Ahmed Aiman; Mohd Zaidi, Mohammad Zairiel Ikhwann; Ramli, Muhamad Qamel; Abd Malik, Mohd Akhmal Daniel; Saidi Azhar, Nur Athirah Laili (2019)
Nourish & Lift Enterprise offers wheelchair products and services for customers, providing the variety wheelchair that gives high satisfaction of consumer. Nourish & Lift Enterprise marketing strategy is to emphasize the quality and price of our products and services. We offer the affordable price because many people in Johor Bahru very low income and poor family. Thus, we develop marketing strategy that gives attraction to come our shop especially poor people. Already we have service and products commitments plan to aggressively build our brand through newspaper, ads and signboard. This loving Wheelchair shop Nourish & Lift Enterprise will provide is sure to appeal to customers throughout the Johor especially Johor Bahru area.